Isolation and characterization of Lupeol from stems of Girardinia diversifolia - Singh, C. J.; Tripathi, Dr. Nisha; Singh, Dr. Rakesh; Singh, Dr. Vartika; K. Rathna; S.T.S. Lepcha; Sharma, Dr. Santosh Kumar; Saini, Dr. Ravinder Kumar; Singh, Richa; Sanjay Singh; Shukla, Dr. Priya (Innovative Research Thoughts, 2018)
Girardinia diversifolia, growing abundantly in the Middle Himalayas, belongs to the family Urticaceae and commonly known as ‘Dans kandali’ in Uttarakhand. A phytochemical investigation of the plant was carried out to ascertain the biochemical setup of the plants. Lupeol, a bioactive triterpenoid, was isolated from the stem extract of Girardinia diversifolia for the first time by extraction and isolation through spectroscopic studies. Present paper discusses the extraction techniques, characterization, chemical and biological properties of the Lupeol and its industrial potential which can be used for taking up future research and development activities for strengthening the existing pharmacological sciences besides, refining and utilizing traditional knowledge for the welfare of the society.